O partido Rússia Unida e as reformas eleitorais na Federação Russa - Pestana, Matheus Cavalcanti (2019)
Vladimir Putin’s “United Russia” party, since its founding, has been the target of several controversies that point it as highly authoritarian and dictatorial, both by media and scholars. Getting the legislative majority in all elections for the State Duma since 2003, “United Russia” has approved reforms that altered the electoral and party system rules. The main suspicion is that the reforms were only to benefit and maintain its majority. The scope of the current dissertation is to evaluate this hypothesis, using the Central Election Comission of the Russian Federation’s electoral data, seeking to measure the impact of each reform on the electoral and party system and representation, looking for the existence of a bias on it that possibly makes the representation disproportional, which would benefit the party. It aims to understand if, in fact, those reforms orchestrated by “United Russia” were made for its own advantage, hampering the rise of other parties to the State Duma and to maintain an artificial majority of Putin’s party in the russian parliament.